2023
DOI: 10.1111/jcpp.13784
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk following self‐harm in young people: a population cohort study using the Northern Ireland Registry of Self‐Harm

Abstract: Background Self‐harm is a recognised predictor of suicide and is most common in those aged under 25 years. The aims of this study were to describe the characteristics of young people who present with self‐harm; quantify the risk of suicide and other causes of death during follow up, and to identify factors associated with mortality risk. Methods The Northern Ireland Registry of Self‐Harm (NIRSH) is a national registry capturing complete data on all presentations made to the 12 Emergency Departments (EDs) in No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In our cohort, we observed high rates of historical self-harm in both self-and clinicianrecorded data. The rates are considerably higher compared to community studies-which have reported aggregate lifetime risk of self-harm in young people between 11.0-17.0% globally [41] -although there is substantial variation in the literature owing to methodological differences between studies [41][42][43][44]. In clinical populations with known mental health problems, it is unsurprising that these risks are higher [45].…”
Section: Discussionmentioning
confidence: 84%
“…In our cohort, we observed high rates of historical self-harm in both self-and clinicianrecorded data. The rates are considerably higher compared to community studies-which have reported aggregate lifetime risk of self-harm in young people between 11.0-17.0% globally [41] -although there is substantial variation in the literature owing to methodological differences between studies [41][42][43][44]. In clinical populations with known mental health problems, it is unsurprising that these risks are higher [45].…”
Section: Discussionmentioning
confidence: 84%
“…Risk factors for self-harm include low socio-economic status, female gender, sexual orientation (LGBT), a history of childhood maltreatment, family history of suicide, bullying, impulsivity, low self-esteem, and mental disorder (Knipe et al, 2022 ; Nock, 2014 ; Stänicke et al, 2024 ). Self-harm is often accompanied by several mental illnesses, and is known to be a risk factor for suicidality (Klonsky et al, 2013 ; Ross et al, 2023 ; Tuisku et al, 2014 ). Particularly, it has been reported that self-harm is related to a wide range of mental disorders such as mood disorders (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Self-harm in childhood and adolescence is a concerning public health phenomenon associated with an increased risk of psychological distress, future self-harm ( Mars et al, 2014 ) and dying by suicide ( Hawton et al, 2020 ; Ross et al, 2023 ). Self-harm is defined in this review as ‘an act with non-fatal outcome in which an individual deliberately initiates a non-habitual behaviour, that without intervention from others will cause self-harm, or deliberately ingests a substance in excess of the prescribed or generally recognised therapeutic dosage, and which is aimed at realising changes that the person desires via the actual or expected physical consequences’ ( Schmidtke et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%